Active lessons for active brains : teaching boys and other experiential learners, grades 3-10 - James, Abigail Norfleet; Allison, Sandra Boyd.; McKenzie, Caitlin Zimmerman (Thousand Oaks, Calif. : Corwin Press, 2011)
'Abigail James, author of the bestselling Teaching the Male Brain, presents this accompanying compilation of middle school language arts and math lesson plans for educators teaching boys. These lessons are based on James' gender research and are applicable for both coed and all male classrooms. Grammar, literacy, algebra, and geometry lesson plans cover the subjects where boys' brains differ the most from their female classmates. These lesson plans offer specific strategies for improving the subject areas where boys often fall behind in by identifying a common weakness of typical boy learners, describing a strategy for working on this weakness, then providing specific examples of that strategy in action'-- Provided by publisher.
Machine generated contents note: AcknowledgmentsAbout the AuthorsIntroduction1. A brief look at experiential learners The Active Brain: Male or Female Language Arts, Mathematics, Science, and Study Strategies Chart: Connects Lessons with Pedagogical Approaches2. Math General Math Algebra Geometry3. Language Arts Reading Writing and Grammar4. Science5. Study StrategiesIndex.
Includes bibliographical references (p. 230-232).
Keywords: Experiential learning; Active learning; Learning, Psychology of; Boys -- Education; Sex differences in education